The Association of Cumulative Fluid Balance and Sepsis Patient Mortality During Treatment in the Intensive Care Unit - Gusriadi B; Syamsul Hilal Salam; Hisbullah Hisbullah; Syafri Kamsul Arif; Muhammad Rum; Ari Santri Palinrungi (Faculty of Medicine, Hasanuddin University., 2022)
Introduction: Fluid management in sepsis patients is crucial, especially in the first three hours after sepsis diagnosis is established. However, excessive fluid administration will increase patient mortality. This study’s purpose is to determine the correlation among cumulative fluid balance and mortality in patients with sepsis and/or septic shock admitted to the Intensive Care Unit (ICU) of Dr. Wahidin Sudirohusodo Central Hospital, Makassar. Methods: This comes about as an analytical observational study with a retrospective method. The population involved in this study was patients diagnosed with sepsis and septic shock who were treated in the ICU of Dr. Wahidin Sudirohusodo Central Hospital, Makassar from January to December 2021 with a total sample of 56 people. Data were analyzed using Mann-Whitney and Chi-Square statistical tests with a significance level of α=0.05. Data were studied using SPSS 25.0 (SPSS, Inc. Chicago, IL). Results: The mean cumulative fluid balance in septic patients was -1299.51±5228.34 ml. Based on the fluid balance category, 24 people (42.9%) had a positive balance and 32 people (57.1%) had a negative balance. There was a correlation among cumulative fluid balance and mortality in sepsis patients hospitalized in the ICU of Dr. Wahidin Sudirohusodo Central Hospital (p < 0.001), out of 24 patients with a positive balance, the non-survivors percentage was 66.7% and 33.3% of patients survived, while out of 32 patients with a negative balance, the percentage of non-survivors was 18.7% and 81.3% of patients survived. Conclusions: There is a correlation among cumulative fluid balance and mortality of septic patients in the ICU. A positive cumulative fluid balance will cause a higher mortality rate or risk of death compared to a negative cumulative fluid balance.